(untitled) (Quest Journal of Management and Social Sciences, 2024)
Background: Mustard oil is used by millions of People in south Asian region due to its health benefit, livelihood and employment opportunities. For smooth operation from growing to reach at customers hand value chain supports a lot. It is not only helping farmers but also generating opportunities in each stage. Thus, this study aims to identify value chain analysis of mustard oil in Nepal. Objective: Aim of this study is to identify the on-Value Chain Analysis of Mustard Oil. Method: The paper followed the design of explanatory research and collected data using structured questionnaires. Binary Logistic Model was used for inferential analysis. Siraha and Saptari Districts are chosen purposely. 164 respondents were conveniently sampled from farmers and traders. Result: The study shows the cooperatives play role in accessing credit, accessing input and training with the help of government and non- government organizations. The study tells us the fact that the mustard value chain functions in a traditional way, there is no innovative way of integrating the chain actors. Though the cooperatives are involved in both input supply and in credit services, their role is not as expected. Farmers are not getting adequate advisory service from cooperatives. Ages, off-farm income, access to information, access to input are the factors that add value in mustard value chain. Conclusion: The study concluded that the value chain is currently underdeveloped; there is no innovative way of integrating the chain actors in value chain. Farmers are not getting adequate advisory service from cooperatives. Paper Types: Research Paper Keywords: Value Chain Analysis, Farmer, Traders, Value addition, Logistic Model, Kobo toolbox. JEL Classification: N55, Q8, Q18 and Q2